Research on physical activity levels of men at the age of fifty and over and comparison of some demographic data - Sefik Ozbek; Muslum Colak; Yunus Oztasyonar; Sebnem Sarvan Cengız; Mehmet Gullu (Türk Spor ve Egzersiz Dergisi)
In this study, we aimed to research physical activity levels of men at the age of fifty and over. The population of study is Şanlıurfa city and sample consists of men aged fifty and over in rest homes and coffee shops. 286 men have participated to this study from amongst the men in the locations stated. International Physical Activity Questionnaire, IPAQ, long form, has been used to analyze physical activity levels of men over the age of fifty. International validity and reliability studies have been implemented by Craig et al., and validity and reliability studies in Turkey have been implemented by Öztürk to university students. Blood pressure, length, weight, hip and waist circumferences have been measured for determining physical characteristics of men at the age over fifty who have participated to the study. Their BMIs have been calculated by using length2 / weight formula. Their hip and waist rates have been calculated from the formula developed by Garner et al. and Singh. In the analysis of the data obtained, % frequency analysis and chi-square test have been applied. As the result of the study that we had implemented, a meaningful relationship has been found between marital status and AO values, education levels and Income levels and AO and MET values of older individuals. It has also been seen that there was a meaningful relationship between cigarette usage and waist circumference, and MET values similarly in respect of statistics.